Copyright and multimedia products : a comparative analysis - Stamatoudi, Irini A. (Cambridge studies in intellectual property rights., 2002)
Multimedia products have experienced tremendous market success. Yet too often they are given inadequate protection under existing national and international copyright schemes. Irini Stamatoudi provides a comprehensive, comparative treatment of multimedia works and copyright protection in this clear and concise volume. A detailed introduction outlines the nature of the multimedia work, as well as the scope of existing legislation; separate chapters consider collections and compilations, databases, audiovisual works and computer programs (video games are here treated as a 'test case'). Stamatoudi then analyses issues of qualification, regime of protection, and offers a model for a European legislative solution. Copyright and Multimedia Products will interest academics and students, as well as practitioners and copyright policy makers.